Os aspectos originais da geografia da França - Jean-Robert Pitte (Confins)
France is a nation, a cultural and political construct which has aggregated diverse territories around the core of the Ile-de-France over a period of a millennium. It has always been divided between centrifugal and centripetal forces, between the concern to respect regional diversity and the state and geographic centralization of which Paris is the powerful symbol. The opening onto three seas and oceans and its position as European finisterre, as well as its Roman and Christian heritage, made France an extroverted country, open to multiple external influences and eager to shine in Europe and in the world.